Pay Flexibility and Government Performance : A Multicountry Study - World Bank (Washington, DC, 2014)
This study examines whether financial incentives through pay flexibility can improve the performance of staff in government bureaucracies. Its main messages for pay policy are pay flexibility can improve performance, pay flexibility works most strikingly in changing managerial behavior. Improving public sector performance does not need to wait for systematic pay rationalization or pay simplification throughout government. Pay flexibility can work with rather than instead of long-term career incentives. The strategy and implementation of pay flexibility reforms must take into account the extent of fragmentation and complexity of the existing public sector pay structure in the country.